Lacunary Statistical Convergence Sequence in Neutrosophic Metric Space - Johnsy, J.; Jeyaraman, M. (Communications in Mathematics and Applications, 2023)
Researchers describe the theory of Lacunary Strongly Convergence ( LSC ) and its application to sequences of sets in Neutrosophic Metric Spaces(NMS). We derive a conceptual connection between these ideas. In addition, that we have defined certain required and adequate criteria to ensure the similarity for Statistical Convergence(StC ) and Lacunary Statistical Convergence(LStC) sets for the sequence of NMS. We develop certain findings along with the idea of enhanced Cesaro summability in NMS.